Faktor-Faktor Penentu Profitabilitas Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia - Atmaja, Ronaldo; Usman, Bahtiar (International Journal of Digital Entrepreneurship and Business, 2023)
This study aimed to investigate the effects of liquidity, intangible assets, working capital, leverage, company size, and efficiency on the profitability of manufacturing companies listed on the Indonesian Stock Exchange (IDX). A purposive sampling method was used to obtain 74 manufacturing companies listed from 2017 to 2021 based on the specified criteria. The sample selection criteria encompassed manufacturing companies listed on the IDX, representing diverse sectors, including the basic and chemical industry, consumer goods industry, and miscellaneous industry. The selection was restricted to companies not undergoing delisting and initial public offering procedures during the research period to ensure a balanced panel data structure, and the financial statements of these companies were required to meet all criteria for each respective variable. Furthermore, the statistical analysis instrument used was panel data regression with a random effect as the best econometric model selected. The results showed that liquidity, working capital, leverage, company size, and efficiency positively affected profitability. The predictor of intangible assets did not significantly affect profitability. Meanwhile, this study was expected to contribute in the form of managerial implications to consider liquidity, working capital, leverage, company size, and efficiency to enhance profitability.